d-chiro-Inositol Attenuates Epinephrine-stimulated Hepatic Glucose Output in the Isolated Perfused Liver Independently of Insulin - Whiting, L.; Danaher, R. N.; Ruggiero, K.; Lee, C.-C.; Chaussade, C.; Mulvey, T.; Phillips, A.; Loomes, K. M. (Hormone and Metabolic Research, 2013)
d-chiro-Inositol (DCI) is a cyclic sugar alcohol that evokes both antidiabetic and insulin sensitizing effects. Pharmacological administration of DCI has been shown to lower blood glucose in rat models of diabetes mellitus and enhance insulin sensitivity in humans with polycystic ovary syndrome (PCOS). We hypothesised that the antidiabetic effects of DCI could be due to inhibition of hepatic glucose output (HGO). To test this hypothesis, we perfused isolated rat livers either with buffer, myo-inositol, DCI, or insulin, and investigated their respective effects on the stimulation of HGO by epinephrine. We found that perfusion with 200 μM DCI attenuated epinephrine-stimulated HGO by 35% over 30 min as compared to the buffer control perfusion (p=0.05). By comparison, perfusion with 1 nM insulin attenuated epinephrine-stimulated HGO by 57% (p<0.0001). The glucose-lowering effects by DCI occurred independently of insulin and were specific to the DCI stereoisomer as 200 μM myo-inositol had no effect. These findings suggest that DCI could evoke its antidiabetic effects in vivo by inhibition of HGO. Further identification of the protein targets involved could open up new avenues to regulate hyperglycaemia with wider implications for the treatment of hepatic insulin resistance in PCOS.